Pengelolaan Limbah Bahan Berbahaya dan Beracun (B3) Medis Pada Masa Pandemi Covid-19 - Febrina, Tia (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
This research aims to identify the effects of hazardous and toxic waste (B3) medical care during the period of the pandemic covid-19 that must be processed according to the rules to prevent it's being abused according to the minister of environment regulation no. 56 of 2015. Problems are focused on the management and synchronization of hazardous and toxic waste management (B3) medical in the covid-19 treatment at RSUD Dr. Achmad Mochtar Bukittingi. The approach method used is an empirical type of juridical that assesses the requirements of the law and what happens in reality in society and is a descriptive analysis that attempts to describe and interpret objects as they are. Data was collected through interviews with the informant, document studies, and qualitative analyses. The study concludes that B3 waste management of the covid-19 patient at RSUD Dr. Achmad Mochtar Bukittinggi for the waste reduction and election stage, as well as from the B3 disposal, processing, and stock-raising of waste b3 was carried out by the third-party waste management provider located on Aia Dingin, Padang. The Synchronicity of B3 waste management refers to the 1945 constitution no. 32 of 2009 on environmental protection and management also refers to other rules such as health ministries, environment and forestry ministries, and regulations like government regulations and licenses.